Strongyloides stercoralis infection: A systematic review of endemic cases in Spain. - Maria Barroso; Fernando Salvador; Adrián Sánchez-Montalvá; Pau Bosch-Nicolau; Israel Molina (Public Library of Science (PLoS), 2019)
BACKGROUND:Strongyloides stercoralis infection, a neglected tropical disease, is widely distributed. Autochthonous cases have been described in Spain, probably infected long time ago. In recent years the number of diagnosed cases has increased due to the growing number of immigrants, travelers and refugees, but endemically acquired cases in Spain remains undetermined. METHODOLOGY:We systematically searched the literature for references on endemic strongyloidiasis cases in Spain. The articles were required to describe Strongyloides stercoralis infection in at least one Spanish-born person without a history of travel to endemic areas and be published before 31st May 2018. Epidemiological data from patients was collected and described individually as well as risk factors to acquisition of the infection, diagnostic technique that lead to the diagnosis, presence of eosinophilia and clinical symptoms at diagnosis. FINDINGS:Thirty-six studies were included, describing a total of 1083 patients with an average age of 68.3 years diagnosed with endemic strongyloidiasis in Spain. The vast majority of the cases were described in the province of Valencia (n = 1049). Two hundred and eight of the 251 (82.9%) patients in whom gender was reported were male, and most of them had current or past dedication to agriculture. Seventy percent had some kind of comorbidity. A decreasing trend in the diagnosed cases per year is observed from the end of last decade. However, there are still nefigw diagnoses of autochthonous cases of strongyloidiasis in Spain every year. CONCLUSIONS:With the data provided by this review it is likely that in Spain strongyloidiasis might have been underestimated. It is highly probable that the infection remains undiagnosed in many cases due to low clinical suspicion among Spanish population without recent travel history in which the contagion probably took place decades ago.